Kendala Pengendalian Pencemaran Total Suspended Solid dan Phosphat di Sub Das Tlaga Ria Sentani Pasca Banjir Bandang - Auldry F Walukow; Triwiyono Triwiyono; Albert Lumbu (Universitas Riau, 2021)
The problem that occurs in Lake Sentani is that it has been contaminated by parameters of TSS, BOD, Pb, Cu, and DO respectively with valuesof 76 mg / L, 4.63 mg / L, 0.035 mg / L, 0.03 mg / L, and 5.72 mg / L because these parameters have exceeded the quality standard according to environmental regulations. This study aims to determine the assimilation capacity of TSS and PO4 parameters and analyze pollution control models in the Tlaga Ria sub-watershed. The research method used to determine the assimilation capacity is a linear regression equation and in analyzing the pollution control model the interpretative structural modeling method is used. The results showed that the TSS assimilation capacity value in Lake Sentani was -12,700 tons/month. The value of water quality in Lake Sentani is above the value of the assimilation capacity, this shows that Lake Sentani has been polluted by TSS parameters. Meanwhile, the value of PO4 parameter assimilation capacity is 44.36 tons/month and since 2016 Lake Sentani has been unable to conduct self purification. The key elements of the Sentani Lake pollution control constraints in the Tlaga Ria watershed are weak implementation of environmental regulations, differences in objectives among stakeholders, differences in objectives between administrative areas, weak support of business owners, conflict of interests, and weak enforcement of regulations.